An Empirical Analysis of Factors Affecting Customer Loyalty to Sea Freight Forwarders in Thailand - Narunart, Teewin (Animo Repository, 2019)
Thailand has become one of the world’s most significant production bases and therefore, must rely on international sea transportation to move cargo. The primary goal of this paper is to develop a structural equation model to examine how service quality, relationship quality, and customer satisfaction affect customer loyalty. The study sampled 2,029 subjects— company managers, service users, and freight forwarders—in three specific industries: computer and electronics components, automotive and original equipment, and agricultural products. It deployed quantitative research methods and applied a seven-point rating scale in a structured questionnaire to analyze the relationships among the variables. The findings indicate that service quality affects both customer satisfaction and relationship quality, which ultimately affect customer loyalty.